Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsami.7b14125
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Cyanine-Loaded Liposome-like Nanocapsules of Camptothecin–Floxuridine Conjugate for Enhanced Chemophotothermal Combination Cancer Therapy

Abstract: A dual-in-dual synergistic strategy was proposed based on the self-assembly of combinatorial nanocapsules (NCs) from Janus camptothecin-floxuridine (CF) conjugate and the near-infrared absorber of 1,1'-dioctadecyl-3,3,3',3'-tetramethylindotricarbocyanine iodide (DiR) by introducing PEGylated phospholipid of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycerol)-2000] to increase the blood circulation time of NCs. Due to the use of amphiphilic CF and DiR themselves to form liposome-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 38 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…It has been reported that anticancer drug combinations simultaneously delivered to tumor cells can afford synergistic therapeutic effects, thus overcoming tumor heterogeneity and drug resistance issues. The combination of irinotecan and a fluoropyrimidine derivative in a synergistic 1:1 molar ratio inside a liposome has been demonstrated to provide greatly enhanced antitumor therapeutic efficacy [30][31][32][33][34] . In this study, a highly symmetric Janus camptothecinfloxuridine (CF) conjugate linked with two hydrophobic camptothecin (CPT) molecules and two hydrophilic floxuridine (FUDR) molecules and with multivalent pentaerythritol through hydrolyzable ester bonds was synthesized using a protection-deprotection strategy [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that anticancer drug combinations simultaneously delivered to tumor cells can afford synergistic therapeutic effects, thus overcoming tumor heterogeneity and drug resistance issues. The combination of irinotecan and a fluoropyrimidine derivative in a synergistic 1:1 molar ratio inside a liposome has been demonstrated to provide greatly enhanced antitumor therapeutic efficacy [30][31][32][33][34] . In this study, a highly symmetric Janus camptothecinfloxuridine (CF) conjugate linked with two hydrophobic camptothecin (CPT) molecules and two hydrophilic floxuridine (FUDR) molecules and with multivalent pentaerythritol through hydrolyzable ester bonds was synthesized using a protection-deprotection strategy [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of irinotecan and a fluoropyrimidine derivative in a synergistic 1:1 molar ratio inside a liposome has been demonstrated to provide greatly enhanced antitumor therapeutic efficacy [30][31][32][33][34] . In this study, a highly symmetric Janus camptothecinfloxuridine (CF) conjugate linked with two hydrophobic camptothecin (CPT) molecules and two hydrophilic floxuridine (FUDR) molecules and with multivalent pentaerythritol through hydrolyzable ester bonds was synthesized using a protection-deprotection strategy [33][34][35] . Its amphiphilic structure facilitates the self-assembly of CF MBs, enabling highly stable codelivery of drug combinations from conjugates with remarkably high drug-loading content (DLC), a fixed CPT/FUDR molar ratio of 1:1 and no premature release (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The combination index (CI) is used to evaluate the synergistic effect of combination therapies. If CI<1, it suggests that different drugs act synergistically; otherwise, that is, if CI=1 or CI>1, the drugs act additively or antagonistically …”
Section: Resultsmentioning
confidence: 99%
“…If CI < 1, it suggestst hat different drugs act synergistically;o therwise, that is, if CI = 1o rC I> 1, the drugs act additively or antagonistically. [38,39] To evaluate the influence of poly-b-CD on the experimental results, we investigated its potential toxicity.T he blank sample of poly-b-CD was incubated with CCRF-CEMa nd Ramos (human Burkitt lymphoma) cell lines for 48 h. With use of a standard MTS assay, the cell viability of cells remained above 80 %, demonstrating that the carrierh ad little cytotoxicity toward these cell lines within ac ertain concentration range ( Figure 3A).…”
Section: Synergistictherapeutic Effects Of Combination Drugsmentioning
confidence: 99%
“…The integration of co-delivered anticancer drugs with cancer imaging agents is an approach that could be of interest. [41][42][43][44][45] However, integrated systems demonstrating PTX/GEM codelivery with cancer imaging agents have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%